Comprehensive workplace intervention for cancer prevention in China (WECAN): protocol for a stepped-wedge, cluster-randomised controlled trial. Issue 4 (25th April 2023) - Li, Yuan; Sun, Kaige; Wang, Baohua; Wang, Ning; Luo, Rong; Wang, Changqiong; Liu, Yu; Duffy, Stephen; MacGregor, Graham A; Wu, Jing; He, Feng J; Zhang, Puhong
Abstract : Introduction: Cancer is the second leading cause of death across the globe with the majority of deaths occurring in low-income and middle-income countries. Evidence has shown that the cancer burden can be substantially reduced by avoiding behavioural risk factors through comprehensive intervention strategies, including workplace health promotion, which has shown to be cost-effective in developed countries while rarely conducted in developing countries. This study aims to explore a feasible and sustainable approach to the prevention and control of cancer in China by developing an evidence-based comprehensive workplace health model equipped with a smartphone application for implementation. Methods and analysis: This study is designed as a stepped-wedge, cluster-randomised controlled trial. We will recruit 15 workplaces from three cities in China. A total of 750 employees will be randomly selected for evaluation that includes five rounds of survey conducted every 6 months. After the second evaluation, workplaces will be randomly allocated to start the intervention sequentially every 6 months in three steps with five workplaces per step. A mobile application 'Healthy Workplace' will be developed to support the intervention. On-line and off-line health-related activities will be carried out among employees. Employers will provide supportive policies, environment and benefits to facilitate the adoption of healthy behaviours. The primary outcome is the change of Healthy Lifestyle Index Score, which consists of five components including smoking, alcohol drinking, physical activity, diet and body mass index. Ethics and dissemination: The study has been approved by Queen Mary University of London Ethics of Research Committee (QMERC22.257) and Chinese Centre for Disease Control and Prevention Institutional Review Board (202210). Written informed consent is required from all participants. Results will be disseminated through presentations, publications and social media. Trial registration number: ChiCTR2200058680.